A rethinking at meaning of judicial activism - Muñoz Mendiola, Julio César (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2020)
This paper proposes a rethinking of the way to understand judicial activism, above all, away from the criticisms that have been developed from different theoretical positions without a strong empirical support, because in the judicial practice into definitive constitutional stage, that activism represents an institutional path for the realization of fundamental rights and democratic society. Thus, judicial activism, as consequence of judicial review, will have an institutional basis that is compatible with the institutional design of the Constitutional State, because that design has conferred discretion on constitutional judges to concretize the content of the Constitution.